Dekolorisasi dan Degradasi Limbah Zat Warna Naftol oleh Jamur dari Limbah Industri Batik - Nurhaedar Nurhaedar; Fahruddin Fahruddin; As'adi Abdullah; Nur Asmasari Syam; Nur Hadijah Talessang (Jurnal Ilmu Alam dan Lingkungan, 2019)
Naphthol color substance is a dye that is widely used in the batik industry and usually waste from batik industry household scale directly discharged into the environment without being processed first. This study was conducted to determine the ability of fungia isolated from batik industrial wastes in Makassar to decolorize and degrade dye naphthol. Isolation of naphthol dye degrading fungi was done by using a PDA medium containing 50 ppm naphthol dye. To determine the ability of decolorization and degradation is done visually and decreasing OD at λ580 at various concentrations. In addition to measuring the growth of biomass fungi and PH. The results showed that decolorization and degradation ability by isolate of SL4 and BK4 fungi isolated from batik waste hence the best result shown by SL4 isolate at naphthol concentration of 20%.